El thelos de la protección de los datos personales ante el derecho al acceso a la información - Javier Nájera Montiel (Ius Humani. Jornal do direito, 2008)
This text aims to analyze and study of three high-profile figures, such as the right to information, personal data and privacy, institutions currently have acquired a transcendental value, resulting in new forms of power and handling, tools and control means. Therefore, we first analyzed the right of access to information and personal data then. End this investigation with the study of privacy, as the axiological aspect of the protection of personal data.